Research on Application of Regression Least Squares Support Vector Machine on Performance Prediction of Hydraulic Excavator - Zhan-bo Chen (Journal of Control Science and Engineering)
In order to improve the performance prediction accuracy of hydraulic excavator, the regression least squares support vector machine is applied. First, the mathematical model of the regression least squares support vector machine is studied, and then the algorithm of the regression least squares support vector machine is designed. Finally, the performance prediction simulation of hydraulic excavator based on regression least squares support vector machine is carried out, and simulation results show that this method can predict the performance changing rules of hydraulic excavator correctly.